Socialization related learning among new staff in Malaysian secondary schools - Abdull Kareem, Omar; Jusoff, Kamaruzaman; Khuan, Wai Bing; Awang, Marinah; Mohamad Yusof, Abdul Raheem; Yunus, Jamal @ Nordin; Yeop Yunus, Nek Kamal (IDOSI Publications, 2011)
Organizational culture is closely related to the socialization process that occurs in organizations. The purpose of this study is to investigate the socialization related learning process among new staff in secondary schools in Peninsular Malaysia. Respondents consist of new school staff categorized as graduate teachers, non-graduate teachers and support staff. The questionnaire was used to investigate the level of learning related to the socialization process among school staff. Four major elements of the socialization related learning are discussed. They include job knowledge, acculturation towards the job and organization, establishing relationship and socialization related learning satisfaction. The finding of this study shows that the level of each element of socialization related learning among the staff was moderate, mean score between 3.3 - 4.01. The one-way ANOVA and t-test that were used to investigate the difference among the four elements in terms of job categories, past experiences, current experience, gender, type of schools and location shows significant differences for most of the elements. The study concluded that the level of socialization related learning among new staff is satisfactory. The study implicated that the level needs to be improved especially for staff from the non-graduate and supporting group which recorded a mean lower mean.